Treatment effects produced by the Bionator appliance. Comparison with an untreated Class II sample - Almeida, M. R.; Henriques, JFC; Almeida, R. R.; Almeida-Pedrin, R. R.; Ursi, W. (Oxford University Press, 2004)
The purpose of this retrospective investigation was to evaluate the dentoalveolar and skeletal cephalometric changes of the Bionator appliance on individuals with a Class II division 1 malocclusion. Lateral cephalograms of 44 patients were divided into two equal groups. The control group comprised 22 untreated Class II children (11 males, 11 females), with an initial mean age of 8 years 7 months who were followed without treatment for a period of 13 months. The Bionator group (111 males, 11 females) had an initial mean age of 10 years 8 months, and were treated for a mean period of 16 months. Lateral cephalometric headfilms were obtained of each patient and control at the beginning and end of treatment.The results showed that there were no changes in forward growth of the maxilla in the experimental group compared with the control group. However, the Bionator treatment produced a statistically significant increase in mandibular protrusion, and in total mandibular and body lengths. There were no statistically significant differences in craniofacial growth direction between the Bionator group and the control group, although the treated patients demonstrated a greater increase in posterior face height. The Bionator appliance produced labial tipping of the lower incisors and lingual inclination of the upper incisors, as well as a significant increase (P < 0.01) in mandibular posterior dentoalveolar height. The major effects of the Bionator appliance were dentoalveolar, with a smaller significant skeletal effect. The results indicate that the correction of a Class II division 1 malocclusion with the Bionator appliance is achieved not only by a combination of mandibular skeletal effects, but also by significant dentoalveolar changes.